Board Gender Diversity as A Moderator in The Effect of ESG Performance on Systematic Risk - Fivi Anggraini; Ferli Meidiana Cahyati; Dwi Fitri Puspa; Meihendri; Aza Azlina Md Kassim (Jurnal Kajian Akuntansi, 2025)
The gender diversity of the board is essential to reduce the systematic risk of manufacturing companies. To mitigate this risk, manufacturing companies in Indonesia need to pay attention to and strengthen environmental, social, and governance (ESG) performance. This study aims to empirically examine the influence of environmental, social, and governance (ESG) performance on systematic risk with gender diversity of the board as moderation in manufacturing companies in Indonesia. The sampling technique used is purposive sampling. The number of samples in this study is 16 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. Data analysis was carried out using the SPSS and Gretl programs. The empirical results of this study provide evidence of the negative influence of environmental and governance performance on systematic risk. However, social performance does not have systematic risk. This study succeeded in proving that the gender diversity of the council moderates the relationship between environmental performance, social performance, and governance performance to systematic risk. This research can be a foundation for companies to strengthen and improve the environmental, social, governance (ESG), and gender diversity performance of the board to reduce systematic risks and meet stakeholders' expectations.